2021
DOI: 10.21470/1678-9741-2020-0408
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Neutrophil-Lymphocyte Ratio Can Predict Outcomes for Patients Undergoing Tetralogy of Fallot Repair

Abstract: Introduction Elevated neutrophil-lymphocyte ratio (NLR) has been associated with poorer outcomes in cyanotic patients undergoing single ventricle palliation. Little is known about this biomarker on patients with tetralogy of Fallot (TOF), the most common cyanotic congenital heart disease. Our objective is to study the impact of preoperative NLR on outcomes of TOF patients undergoing total repair. Methods This retrospective study included 116 consecutive patients between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…27 In 2020, we studied 116 children after TOF repair and found that an NLR value > 0.8 was associated with longer ICU (P = .03) and hospital LOS (P = .001). 29 Further evaluation of this group of patients demonstrated that a higher NLR was associated with grade III AKI (P = .040). 33…”
Section: Cyanotic Chdmentioning
confidence: 87%
See 4 more Smart Citations
“…27 In 2020, we studied 116 children after TOF repair and found that an NLR value > 0.8 was associated with longer ICU (P = .03) and hospital LOS (P = .001). 29 Further evaluation of this group of patients demonstrated that a higher NLR was associated with grade III AKI (P = .040). 33…”
Section: Cyanotic Chdmentioning
confidence: 87%
“…Of 404 cyanosis patients (44.9%) in 6 studies, 24,26,27,29,31,33 210 patients underwent CHD repair and 194 patients underwent surgical palliation (Table 1). A total of 193 patients (50.2%) were noted to have TOF.…”
Section: Prognostic Value Of Nlr In Congenital Heart Surgerymentioning
confidence: 99%
See 3 more Smart Citations